2016
DOI: 10.4274/jus.971
|View full text |Cite
|
Sign up to set email alerts
|

Ureteroscopy Outcomes, Complications and Management of Perforations in Impacted Ureter Stones

Abstract: İmpakte üreter taşı olan hastalara yapılan üreteroskopinin sonuçlarını ve gelişen perforasyonların yönetimini değerlendirmeyi amaçladık. Gereç ve Yöntemİmpakte üreter taşı için opere edilen 81 hastanın verileri retrospektif olarak incelendi. Operasyon sırasında gelişen komplikasyonlar görsel olarak değerlendirildi, gereğinde retrograd üreterografi çekildi. Perforasyonun üreter çevresinin %50'sinden küçük olduğu yaralanmalara minör, büyük olmasına da majör perforasyon denildi. Perforasyonun evresine göre sadece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…After eliminating non-eligible studies, we identified five articles addressing ureteral stricture formation following therapy for impacted ureteral stones (Table 1) [6,[9][10][11][12]. Our study selection is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After eliminating non-eligible studies, we identified five articles addressing ureteral stricture formation following therapy for impacted ureteral stones (Table 1) [6,[9][10][11][12]. Our study selection is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…In their retrospective study, Bayar et al [10] discovered that ureteral perforation during ureteroscopy for impacted ureteral stones was one of the main causes leading to ureteral strictures. They reported that the ureteral stricture rate was almost 14-fold higher in patients who experienced ureteral perforation during ureteroscopy than in patients who did not, 5.6% vs. 80% [10].…”
Section: Resultsmentioning
confidence: 99%